Melampaui Motivasi: Bagaimana Stres Kerja dan Disiplin Kerja Membentuk Kinerja Karyawan pada Layanan Kurir - Bayu Prasetyo, Rival; Ratnawati, Shinta; Marlina Verawati, Dian (Jurnal Manajemen dan Bisnis Kreatif, 2026)
This study examines declining employee performance driven by high inbound-related workloads, employee tardiness, low compliance with work regulations, and missed company-set targets. This study aims to examine the effects of job stress, work discipline, and work motivation on employee performance in the Inbound Department of the JNE Magelang Branch's Head Office. The research employed a quantitative method using saturated sampling, involving the entire employee population of 46 respondents. Research data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 25. The results indicate that job stress does not affect employee performance. However, work discipline and work motivation have a positive and significant effect on employee performance.